2016
DOI: 10.19082/2208
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to develop and promote public-private partnerships (PPPs) in the provision of hospital services in Iran: a qualitative study

Abstract: IntroductionPublic-Private Partnerships (PPPs) have been constructively considered in recent years to reform health sectors in many countries. This study aimed at explaining the strategies to develop and promote PPPs in the provision of hospital services in Iran.MethodsThis qualitative study was conducted in 2015. The study population consisted of experts and professionals of the health system and individuals familiar with PPPs and roles in the development of such models in hospital services in Iran that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…[45][46][47] There are different studies about 3P in Iran, especially about the health sector. 48,49 It seems that the Iranian Government has tried to remove some of the abovementioned obstacles while responding to COVID-19 through several measures, such as reducing import duties, reducing bureaucracy to obtain the required industry licenses, and supporting knowledge-based companies fulfilling technology-based needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47] There are different studies about 3P in Iran, especially about the health sector. 48,49 It seems that the Iranian Government has tried to remove some of the abovementioned obstacles while responding to COVID-19 through several measures, such as reducing import duties, reducing bureaucracy to obtain the required industry licenses, and supporting knowledge-based companies fulfilling technology-based needs.…”
Section: Discussionmentioning
confidence: 99%
“…Sadeghi et al (2016) introduced 4 strategies to develop and promote 3P in the provision of hospital services in Iran, including modifying the policies and regulations, sociocultural changes, improvement of current mechanisms and processes, and financial and capital capacity building 48. Danaei et al indicated 9 barriers to the development of 3P in Iran, including the following:• Economic barriers (ie, bad economic and trade conditions in Iran) • Political barriers (ie, cancellation of government agreements as a result of government change) • Legal barriers (ie, lack of a clear legal framework) • Structural barriers (ie, lack of specialized and professional institutions for 3P projects) • Procedural barriers (ie, low capacity and skills of the public sector to manage public-private partnership projects) • Strategic barriers (ie, government policy in providing infrastructure) • Executive barriers (ie, complexity of tax status of public-private partnership projects) • Human barriers (ie, poor understanding of politicians and decision-makers on 3P) • Sociocultural barriers (ie, low motivation of the private sector in partnership with the public sector) 50…”
mentioning
confidence: 99%
“…PPPs have been used to encourage and facilitate innovations in many healthcare fields. PPPs in public health research [27] have included finding vaccines against, and drugs to treat, communicable diseases [28,29], personalised medicine development [30] and management and infrastructure growth [31,32]. The biggest controversies and expectations concern building and operating healthcare infrastructure, such as hospitals.…”
Section: The Concept Of Ppps In Healthcarementioning
confidence: 99%
“…However according to WHO, more than 38% of medical equipment are out of service (4) and of which 39% is because of users' poor expertise. As such, 50-80% of this resource wastage is due to the improper use and inappropriate technical repair (5)(6)(7)(8). According to the recent studies, 75% of complaints against radiologists are about wrong diagnosis (9)(10), mainly because of poor technique or poor image quality (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%